Asian consensus on irritable bowel syndrome - Gwee, Kok-Ann; Bak, Young-Tae; Ghoshal, U.C.; Gonlachanvit, S.; Lee, O.Y.; Fock, K.M.; Chua, A.S.B.; Lu, Ching-Liang; Goh, Khean-Lee; Kositchaiwat, C.; Makharia, G.; Park, Hyo-Jin; et al. (Blackwell Publishing, 2010)
Background and Aims: Many of the ideas on irritable bowel syndrome (IBS) are derived from studies conducted in Western societies. Their relevance to Asian societies has not been critically examined. Our objectives were to bring to attention important data from Asian studies, articulate the experience and views of our Asian experts, and provide a relevant guide on this poorly understood condition for doctors and scientists working in Asia. Methods: A multinational group of physicians from Asia with special interest in IBS raised statements on IBS pertaining to symptoms, diagnosis, epidemiology, infection, pathophysiology, motility, management, and diet. A modified Delphi approach was employed to present and grade the quality of evidence, and determine the level of agreement. Results: We observed that bloating and symptoms associated with meals were prominent complaints among our IBS patients. In the majority of our countries, we did not observe a female predominance. In some Asian populations, the intestinal transit times in healthy and IBS patients appear to be faster than those reported in the West. High consultation rates were observed, particularly in the more affluent countries. There was only weak evidence to support the perception that psychological distress determines health-care seeking. Dietary factors, in particular, chili consumption and the high prevalence of lactose malabsorption, were perceived to be aggravating factors, but the evidence was weak. Conclusions: This detailed compilation of studies from different parts of Asia, draws attention to Asian patients' experiences of IBS.